Answer:
Common difference = 2
First term = 3.
Explanation:
3rd term = a1 + (3 - 1)d = 7 where a1 = first term and d = the common difference.
Sum of the first 12 terms = (12/2)[2a1 + (12-1)d] = 168
so 6(2a1 + 11d) = 168
So simplifying, we have the following system:
a1 + 2d = 7 ..................(A)
12a1 + 66d = 168
2a1 + 11d = 28.................(B) Multiplying equation A by - 2:
-2a1 - 4d =- -14 Adding this to equation B
7d = 14
d = 2
Now plug this into equation A:
a1 + 2(2) = 7
a1 = 7-4
a1 = 3.